Non-Invasive Technological Innovation for Blood Glucose Monitoring in COVID-19 Patients with Diabetes Mellitus during Pandemic - Melati, Azalia; Aghnia, Nuraulia; Sri, Septiani; Pebrianti, Sandra (International Journal of Nursing and Health Services (IJNHS), 2022)
Background: Glycemic control procedures may help reduce the risk of worsening conditions and death in COVID-19 patients with Diabetes Mellitus (DM). Currently, non-invasive blood glucose monitoring technology has been developed to address the challenges of glycemic control in DM patients. Objective: This literature review aims to identify non-invasive technology innovations for blood glucose monitoring applied to COVID-19 patients with DM comorbidities. Method: The method used is a rapid review by searching for articles on EBSCO-host Academic Science Completed, PubMed, Sage Journals, ScienceDirect, and Taylor & Francis. The study reviewed is scoping the innovation of non-invasive blood glucose monitoring technology with research designs of Randomized Control Trial, Quasi Experiment, Cross-Sectional, and Cohort Study in English with full text, and published from 2019–2021. Results: It was found that there were four types of technology and two biomarkers used for non-invasive blood glucose monitoring, namely Skin Autofluorescence, Microperimetry, Raman Spectroscopy, Mid-Infrared Quantum Cascade Laser Technology, and as well as saliva and exhaled Volatile Organic Compound. Recommendation: Further research is needed to confirm the effectiveness of this device, mainly to prevent death in COVID-19 patients with DM comorbid.